DAMPAK LINGKUNGAN DARI PENGEMBANGAN EKOWISATA BAHARI DI KAWASAN KONSERVASI LAMUN TRIKORA, BINTAN, KEPULAUAN RIAU - Aras Mulyadi; Dessy Yoswaty; Ilham Ilahi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This research was conducted on August - September 2016 in Teluk Bakau Village area, Malang Village Meeting and Desa Berakit. It’s was aimed to provide an overview of socioeconomic conditions of society and ecological status, coastal ecosystem conditions, especially seagrass structure and mangrove structures, and threats of coastal ecosystems and the threat of solid waste around marine ecotourism areas in the Trikora Seagrass Conservation Area, Bintan, Riau Islands. The method used by survey methods, socio-economic condition of the community and the ecological status of the Seagrass Conservation Area Trikora, Bintan, Riau Islands support for the development of marine ecotourism. Based on research results The density value of the species and the percentage of seagrass cover of this area ranged between 86.00-301.56 buds / m2 and 45.90% - 101.43%, respectively. Kerapatan mangrove vegetation tree class 583.59 Ind / Ha with vegetation species dominance Rhizophora apiculatadan Bruguiera gymnorrhiza with INP value respectively Rhizophora apiculata dalah 155-157.47% and 46.11 - 106.23%. The threat of coastal ecosystems in this region is mainly pollution, degradation and degradation of coastal ecosystems, and biota degradation. Threats sourced from the development of marine ecotourism areas in the form of hotel, lodging and reseort construction and its facilities, due to the activities of tourists, fishing activities and the local population. Waste on the dominant in this area are materials of plastic type, wood, paper and stairioform; Then other materials such as glass, rubber cans and cloth.